B cell lymphogenesis in swine is located in the bone marrow - Sinkora, Marek; Sinkorova, Jana (Journal of immunology (Baltimore, Md., 2014)
A course and a site of B cell development in swine are not firmly known. In this study, we show that B cell lymphogenesis is located in the bone marrow (BM). According to expression of MHC class II (MHC-II), CD2, CD21, CD25, CD45RC, CD172a, swine workshop cluster (identification number) (SWC) 7, and μHC, porcine BM cells were resolved into seven subsets representing sequential stages of development. Profile of rearrangement-specific products and transcripts from sorted BM cells confirmed the proposed developmental pathway. The same developmental pathway was further proven by analysis of selection for productive rearrangements in Ig H chains and also by cultivation studies. Cultivation also showed that earliest precursors with incomplete DJ rearrangements can still revert their B cell differentiation and develop along myeloid lineage, whereas this is impossible for later developmental stages. Proliferation and the apoptotic potential of individual developmental stages as well as critical checkpoints were also identified. Colocalization experiments showed early colocalization of MHC-II/CD2/CD172a is replaced by colocalization of MHC-II/CD2/CD21/SWC7/IgM in immature cells, whereas CD25 and CD45RC did not colocalize with any other studied molecules. In this study, we also finally prove that the BM in pigs is fully functional in adult animals and that B lymphogenesis occurs there throughout life. To our knowledge, this is the first study showing a course and a direct site of B cell lymphogenesis in swine.
Keywords: buňky kostní dřeně; imunofenotypizace; Germ-Free Life; B-Lymphocyte Subsets; novorozená zvířata; MHC antigeny II. třídy; Cell Differentiation; těžké řetězce imunoglobulinů; zvířata; Animals, Newborn; primární buněčná kultura; Gene Expression Regulation, Developmental; CD antigeny; Primary Cell Culture; vývojová regulace genové exprese; Antigens, CD; hysterektomie; Swine; Histocompatibility Antigens Class II; prasata; podskupiny B-lymfocytů; gnotobiologické modely; Immunophenotyping; Immunoglobulin Heavy Chains; Animals; buněčná diferenciace; Hysterectomy; Bone Marrow Cells